A case report of Megalencephalic leukoencephalopathy with subcortical cysts, a rare inherited autosomal recessive leukodystrophy, in a Nepalese child - Bhattarai, Manoj; Bhattarai, Ashish Mohan (Journal of Nobel Medical College, 2018)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare inherited autosomal recessive leukodystrophy due to mutations in MLC1 or HEPACAM gene and have typical and characteristic neuroimaging findings. This article reports a case of 13 months old Nepalese male child with diagnosis of MLC. Journal of Nobel Medical College Volume 6, Number 2, Issue 11, July-December 2017, 72-75